Efficiency of night shifts in Primary Healthcare Centers, Aseer Region, Saudi Arabia: Data envelopment analysis - Abdullah A. Saeed; Yahia M. Al Khaldi; Tariq A.I. Falqi; Mohammed A. Qarnan; Zaid S. Alharthi; Abdullah A. Alshafea (Journal of Family and Community Medicine)
BACKGROUND: Efficient allocation of healthcare resources is essential for meeting the increasing demand for healthcare services. This study aimed at exploring the performance of both one- and two-shift Primary Healthcare Centers (PHCCs) and examining the efficiency of healthcare centers to discover how efficiency is affected by the levels of resource allocation and staffing. MATERIALS AND METHODS: The study was conducted at 31 PHCCs assigned to cover extended hours, from 4:00 PM to 8:00 AM during May-October 2023. Study employed a quantitative approach and the data envelopment analysis technique to assess the efficiency of PHCCs, specifically focusing on night shift performance. Data were collected through interviews and surveys with primary healthcare staff including 99 doctors, 119 nurses, and 139 support staff using structured questionnaire. The DEA technique was utilized to measure the relative efficiency of the PHCCs by comparing the inputs and outputs. RESULTS: Out of 31 PHCCs, 45.2% run two shifts. Over the reported period, a total of 126,619 patient visits were recorded; 81.7% came to the two-shift PHCCs and 18.3% to the one-shift PHCCs. On average, each two-shift PHCC received approximately 161 visits/ shift, and the one-shift received 123 visits. Upper respiratory tract infections accounted for 30% of morbidities and chronic diseases for more than 20%. The performance of the two-shifts PHCCs revealed varying levels of efficiency with a score of 1.00 for the most efficient PHCC and 0.31 for the least efficient PHCC. CONCLUSION: This study underscores the importance of data-driven decision-making for healthcare administrators. Ongoing assessments and benchmarking are essential for continuously improving the quality of healthcare service and optimizing utilization of resources. Future research in this field can further explore the factors that contribute to healthcare efficiency and provide deeper insights into healthcare resource management and optimization of service delivery.